Ethnobotany and conservation of indigenous edible fruit plants in South Aceh, Indonesia - Adi Bejo Suwardi; ZIDNI ILMAN NAVIA; TISNA HARMAWAN; SYAMSUARDI; ERIZAL MUKHTAR (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Suwardi AB, Navia ZI, Harmawan T, Syamsuardi, Mukhtar E. 2020. Ethnobotany and conservation of indigenous edible fruit plants in South Aceh, Indonesia. Biodiversitas 21: 1850-1860. The traditional knowledge system is immensely important in the context of plant resource conservation, utilization, and environmental management. The objectives of this study, therefore, were to document local knowledge on the diversity, utilization and sustainable management of indigenous fruit yielding species in the South Aceh region of Indonesia. This research was based on extensive field surveys, plant collection, and interviews with the local people, and a total of 56 indigenous edible fruit species belonging to 24 families were identified. Furthermore, the recognized varieties have numerous applications and serve multiple use categories. For example, they have been adopted as food (56 species), by medicine (16 species), construction materials (14 species), furniture (13 species) and firewood (12 species). These indigenous edible fruits are mostly used in the treatment of cough, stomach ache, diarrhea, fever, and digestive problems, and the following species are commonly traded in traditional markets Durio zibethinus, Garcinia mangostana, Mangifera indica, Mangifera foetida, Mangifera odorata, Baccaurea macrophylla, and Baccaurea lanceolata. The agricultural expansion activities in South Aceh region are assumed to present significant threats to the sustainability of indigenous edible fruit species. Conservation of indigenous fruit plants can be performed through the preservation of traditional knowledge and the promotion and domestication of indigenous fruit plant species.